(untitled) (Nexus International Journal of Science and Education, 2024)
The study aimed to determine the extent of principle centered effectiveness and the extent of leadership characteristics of public elementary school heads. This study employed a non-experimental quantitative research design utilizing descriptive-correlation method. Validated questionnaire and Universal sampling procedure were utilized considering the minimal number of teachers in the research locale. One hundred twenty (120) public elementary school teachers were the respondents of the study. Using mean, pearson-r, and regression analysis, the findings revealed that the principle centered effectiveness was extensive while the extent of leadership characteristics of public elementary school heads was also extensive. Moreover, the overall results disclosed that indicators for the principle centered effectiveness were positively correlated to the leadership characteristics of public elementary school heads. Further, results from the regression analysis revealed the following have a strong influence of principle centered effectiveness on the leadership characteristics of public elementary school heads: instructional program, learners’ personnel administration, and financial and physical support. It is recommended that the school heads should involve the school community in the process of developing a shared vision that aligns with the core values and principles of the school. This collaborative approach encourages ownership, engagement, and commitment from all stakeholders, leading to a more effective and purpose-driven school.